SARS-CoV-2 Variants of Concern Increased Transmission and Decrease Vaccine Efficacy in the COVID-19 Pandemic in Palembang Indonesia - Ghiffari, Ahmad; Anwar, Chairil; Hasyim, Hamzah; Iskandar, Iskhaq; Kamaluddin, Muhammad Totong (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The number of COVID-19 cases surging despite the large scale of health promotion campaigns. This study aimed to find disease transmissibility and affected vaccine efficacy associated with the mutation of the SARS-CoV-2 variant of concern.Methods: The study was a descriptive temporal survey design with secondary ecological data: the whole-genome sequence (WGS) from the Global Initiative on Sharing Avian Influenza (GISAID) and COVID-19 data from the Palembang City Health Office website. Bioinformatics software was used to detect mutations.Results: Palembang submitted 43 whole genome sequences, 13 of which were Pangoline sequences classifications.Conclusions: The two concern variations, Alpha and Delta, were associated with increased transmissions and decreased vaccination efficacy using temporal analysis. Regulations governing the relaxation of mobility restrictions should be based on high rates of testing and tracing, and universal vaccination programs should require that all received two doses of any vaccines as fast as possible.